2016
DOI: 10.5194/bg-13-3847-2016
|View full text |Cite
|
Sign up to set email alerts
|

Spaceborne potential for examining taiga–tundra ecotone form and vulnerability

Abstract: Abstract. In the taiga-tundra ecotone (TTE), site-dependent forest structure characteristics can influence the subtle and heterogeneous structural changes that occur across the broad circumpolar extent. Such changes may be related to ecotone form, described by the horizontal and vertical patterns of forest structure (e.g., tree cover, density, and height) within TTE forest patches, driven by local site conditions, and linked to ecotone dynamics. The unique circumstance of subtle, variable, and widespread veget… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Arctic tundra greening was also observed or simulated at the circumpolar Arctic region [5][6][7][8], Eurasian Arctic [9][10][11], Alaska [2,12,13], and Canada [14]. It is speculated that a positive NDVI trend may be in response to climate warming or reduced snow cover, which would lead to the expansion of vegetation in the tundra [15][16][17][18][19], changing phenological periods [20,21], increased biomass [22,23], and surface water variation associated with thermokarst [24]. Since 2011, regional surface browning trends have been observed that have reversed the direction of the Arctic greening trend after nearly 33 years [4,5,25,26].…”
Section: Introductionmentioning
confidence: 90%
“…Arctic tundra greening was also observed or simulated at the circumpolar Arctic region [5][6][7][8], Eurasian Arctic [9][10][11], Alaska [2,12,13], and Canada [14]. It is speculated that a positive NDVI trend may be in response to climate warming or reduced snow cover, which would lead to the expansion of vegetation in the tundra [15][16][17][18][19], changing phenological periods [20,21], increased biomass [22,23], and surface water variation associated with thermokarst [24]. Since 2011, regional surface browning trends have been observed that have reversed the direction of the Arctic greening trend after nearly 33 years [4,5,25,26].…”
Section: Introductionmentioning
confidence: 90%
“…For example, LAI and the fraction of absorbed photosynthetically active radiation (fAPAR) are critical constraints on carbon cycling and have been derived from a variety of sensors (Myneni et al, ; Zhu et al, ). Properties such as percent tree cover (Montesano et al, ) and land cover type, including forest genera and even species (Beaudoin et al, ), are essential for quantifying large‐scale vegetation distributions and their changes. Finally, forest volume characteristics, such as biomass, tree height, and related canopy properties, can be derived most successfully from lidar (Neigh et al, ).…”
Section: Observing Properties Of the Abz Landmentioning
confidence: 99%
“…Landsat science was revolutionized in 2008 when the USGS provided open access to the archive in a consistent and user‐friendly format (Kennedy et al, ; Wulder et al, ). With subsequent consolidation of the Landsat archive (Wulder et al, ) and increases in computing power, a variety of processing tools (e.g., Google Earth Engine) and circumpolar data products related to tree cover, productivity, and disturbance history (e.g., Hansen et al, ; Ju & Masek, ; Montesano, Sun, et al, ; Sexton et al, ; White et al, ) are now available to the community. Although at a much coarser spatial resolution (1–8 km), the AVHRR family of satellites has provided continuous data since 1978, and particularly since 1981 with the operation of AVHRR/2 on board NOAA‐7.…”
Section: Observing Properties Of the Abz Landmentioning
confidence: 99%
“…How fast vegetation communities can follow their shifting climate envelope in a changing environment is determined by their ability to migrate. This is exceptionally challenging under current global change and plants might strongly lag behind their moving climate envelope (Harsch et al, 2009;Loarie et al, 2009;Moran and Clark, 2012). Temperatures are increasing most strongly in the Arctic.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades treeline stands in the Siberian Arctic were densifying, but only rather slowly colonizing the tundra (Frost et al, 2014;Kharuk et al, 2006;Montesano et al, 2016), which could be attributed to seed limitation (Wieczorek et al, 2017). We developed the Larix vegetation simulator, LAVESI, to simulate tree stand dynamics at the Siberian treeline on the southern Taymyr Peninsula and use it as a framework to explore impacts of climate change on larch forests .…”
Section: Introductionmentioning
confidence: 99%